Software Tool for Brain Morphometry Analysis - Liew, Qiao Jun (Universiti Teknologi PETRONAS, 2017)
Brain morphometry is a technique to study and analyse parameters such as the volume, orientation, position, cross-sectional area, and thickness of the sub-cortical brain regions. It is used to investigate the signature changes of brain regions or the brain abnormalities and is a potential biomarker of diseases in clinical practice. Although there are open source tools exist to perform the brain morphometry analysis, clinicians do not have access of it due to the tools are hard to use and some of the tools do not provide the normal group database for comparison. Clinicians require a visualization and workflow tool in an easy to use format to allow them to investigate shape changes in the subcortical region. In this thesis, we studied 20 healthy control subjects (10 females and 10 males, range of age:19-55).